Implementasi Metode Simple Additive Weighting pada Sistem Pendukung Keputusan Penerima Beasiswa - Faizah, Nur; Prastyanto, Dhidik; Adi, Slamet Seno (Edu Komputika Journal, 2017)
This study aims to get the program decision support system (DSS) that implement simple additive weighting method (SAW) to select recipients. In pursuit of this study using waterfall development model. Based on the foundation of systems development waterfall model, the research begins with an analysis system planning. After analyzing the system followed by designing the system, then the coding and ends with the testing process. SPK recipients of this scholarship using SAW method using 8 criteria. In this research has been conducted trials using criteria 8 and 9 criteria. Implementation method of SAW on SPK recipients are in compliance, as evidenced by the system is capable of providing recommendation recipients. This is indicated by the results of blackbox testing that all functions can be run well. In testing efficiency, obtained the average load time of 1.5 seconds (acceptable) and the average grade obtained acquire grade A. Tests portability states the system can run on multiple web browsers and declared the usability testing criteria are eligible. In the SPK recipients also include additional flexibility criteria up to 20 criteria.